Pola konsumsi pangan berdasarkan pendapatan masyarakat pesisir di Sulawesi Tenggara, Indonesia - Riani, Irdam; Maruf, Amar; Masri, Fina Amalia; Patiung, Seventry Meliana (Universitas Halu Oleo, 2024)
Coastal Communities have typical food consumption pattern that is determined by differences in primary livelihoods, income and food habit. However, fewer studies have been conducted to reveal the relationship between food consumption pattern and income level especially in developing countries. Therefore, this study is relevant to be carried out. This research, applying a mixed quantitative and qualitative method, was conducted in six regencies of Southeast Sulawesi in 2013-2018. A total of 185 respondents were participated through semi-structured interviews and filling questionnaire sheets. The findings from the fieldwork were enriched by the results of field observation and the literature study. This research highlighted that staple food such as rice, cassava, sago, and fish, and also vegetables, sugar, instant noodles and snacks have dominated the coastal dwellers’ diet. Moreover, more than a half of coastal dwellers income (52,76%) has been allocated for food consumption. Based on analysis, it is evident that expenditure for food consumption rises if income level surges as well. If income level increases 1%, then food consumption of the coastal dwellers also raises 0,661%. Keywords: Food Consumption Pattern, Income Level, Coastal Communities, Southeast Sulawesi